Differentiating Real Versus Unreal in Children: An Investigation Using GIF Stimuli - Rohit Bhattacharya; Ritwik J.; Rajkumar; Netra; Abhishek B.P. (International Journal of Children, 2024)
Virtual Reality Judgment is a part of cognitive development. With advancing cognitive development children will develop judgmental abilities enabling them to differentiate realty vs myth. This study explores the development of reality judgment abilities in typically developing children aged 3-6 years. Reality judgment, encompassing both character and action ability perception, is crucial for a child's accurate perception of the world. Existing research on reality judgment often stems from Western contexts, and the study addresses the need for cultural sensitivity in investigating these abilities. Using a sample of 30 participants divided into different age groups (4-5 years and 6-7 years), the study employs a reality judgment task with GIF stimuli to assess participants' discernment between realistic and unrealistic actions. Results indicate significant age-related differences in reality judgment abilities, with the older age group outperforming the younger ones. The stimulus sets, comprising both realistic and unrealistic GIFs, further highlight the nuanced nature of children's judgments. The research uses non-parametric statistical tests, and the results show a substantial difference between the age groups overall. Group comparisons through Mann Whitney U tests confirm the disparities between each pair of age groups. The results highlight how reality perception skills develop in children with regular development. Younger participants struggle with accurately discerning realistic actions, often providing inconsistent justifications. In contrast, older children exhibit improved performance but still face challenges in articulating reasons for labeling stimuli as incorrect. The study contributes valuable insights into the age-related progression of reality judgment.
Keywords: GIF stimuli; age-related differences; cognitive development; perception; reality Judgement